Fatigue in children with perinatal stroke: clinical and neurophysiological associations. (20th June 2019) - Wrightson, James G; Zewdie, Ephrem; Kuo, Hsing‐Ching; Millet, Guillaume Y; Kirton, Adam
Abstract : Aim: To characterize fatigue in children with hemiparesis with perinatal stroke and explore associations with measures of motor performance and corticospinal excitability. Method: Forty‐five children (16 females, 29 males), aged 6 to 18 years (mean [SD] 12y [4]), with magnetic resonance imaging‐confirmed perinatal stroke participated. Associations between fatigue (Pediatric Quality of Life Inventory Version 3.0 cerebral palsy module fatigue subscale), motor performance (Assisting Hand Assessment [AHA], Box and Blocks Test, grip strength), and excitability of corticospinal projections to both hands were examined using ranked tests of correlation, robust regression, and the Mann–Whitney U test. Results: Nearly half of the participants ( n =21) reported experiencing fatigue in the previous month. Function in the less affected hand (Box and Blocks Test, grip strength) was correlated with fatigue scores. Participants with preserved ipsilateral projections to the more affected hand had less fatigue, and scores correlated with the excitability of these projections. Fatigue scores were not associated with age, sex, or AHA score. Interpretation: Fatigue is common in children with hemiparesis with perinatal stroke and is associated with motor performance and the presence and excitability of ipsilateral corticospinal projections from the contralesional hemisphere to the more affected hand. What this paper adds: Fatigue is common in children with hemiparesis with perinatal stroke. Fatigue was associated with motor performance and strength in the less affected, but not the more affected, hand. Fatigue was associated with the presence and excitability of ipsilateral corticospinal projections from the contralesional hemisphere. What this paper adds: Fatigue is common in children with hemiparesis with perinatal stroke. Fatigue was associated with motor performance and strength in the less affected, but not the more affected, hand. Fatigue was associated with the presence and excitability of ipsilateral corticospinal projections from the contralesional hemisphere. This article is commented on by Stubberud on page 158 of this issue.